2020
DOI: 10.3389/fcell.2020.00067
|View full text |Cite
|
Sign up to set email alerts
|

Fc-Linked IgG N-Glycosylation in FcγR Knock-Out Mice

Abstract: Immunoglobulin G (IgG) is the most abundant immunoglobulin isotype in the blood and is involved in the pathogenesis and progression of various diseases. Glycosylation of the IgG fragment crystallizable (Fc) region is shown to vary in different physiological and pathological states. Fc N-glycan composition can alter the effector functions of IgG by modulating its affinity for ligands, such as Fcγ receptors (FcγRs). However, it is not known whether IgG glycosylation is affected by the available repertoire of Fcγ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…IgG-associated bi-antennary glycan structure composition modulates IgG-FcgR binding (Anthony et al, 2012;Dekkers et al, 2017;Wang and Ravetch, 2019), suggesting that when present in these glycan structures, a-gal might modulate IgG effector function. Consistent with previous reports (de Haan et al, 2017;Zaytseva et al, 2020), a-gal was associated to the H chain of IgG from Ggta1 +/+ mice, as detected using a a-galspecific mAb (Figure 5D) or the Bandeiraea simplicifolia lectin (BSIB4) (Figure S5D), the specificity of which was confirmed using a-gal-conjugated bovine serum albumin (BSA) (Figure S5E). Binding of recombinant mouse FcgRIV to plate-bound IgG from Ggta1 À/À mice was enhanced when compared with IgG from Ggta1 +/+ mice (Figure 5E).…”
Section: Loss Of Agal Expression Enhances Igg Effector Functionsupporting
confidence: 92%
See 1 more Smart Citation
“…IgG-associated bi-antennary glycan structure composition modulates IgG-FcgR binding (Anthony et al, 2012;Dekkers et al, 2017;Wang and Ravetch, 2019), suggesting that when present in these glycan structures, a-gal might modulate IgG effector function. Consistent with previous reports (de Haan et al, 2017;Zaytseva et al, 2020), a-gal was associated to the H chain of IgG from Ggta1 +/+ mice, as detected using a a-galspecific mAb (Figure 5D) or the Bandeiraea simplicifolia lectin (BSIB4) (Figure S5D), the specificity of which was confirmed using a-gal-conjugated bovine serum albumin (BSA) (Figure S5E). Binding of recombinant mouse FcgRIV to plate-bound IgG from Ggta1 À/À mice was enhanced when compared with IgG from Ggta1 +/+ mice (Figure 5E).…”
Section: Loss Of Agal Expression Enhances Igg Effector Functionsupporting
confidence: 92%
“…In mammals that carry a functional GGTA1 gene, IgG bi-antennary glycan structures can contain a-gal (de Haan et al, 2017;Zaytseva et al, 2020), raising the possibility of aGal modulating IgG effector function. We found that the deletion of the Ggta1 gene enhances resistance to bacterial sepsis in mice via a mechanism associated with an increase of IgG binding to FcgR, presumably enhancing IgG effector function.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction of antibodies and Fc-receptors is crucial for several antibody effector functions such as antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC) [ 19 ]. Antibodies of the IgG2b and IgG2c isotype were the dominant subclasses induced after vaccination with either of the three adjuvants used and are known to bind to all four FcγR types.…”
Section: Resultsmentioning
confidence: 99%
“…We detected comparable anti-vimentin antibody titers in the serum of vaccinated mice ( Figure 2 A) and could confirm that both adjuvants resulted in the generation of IgG2b and IgG2c antibodies. Since these isotypes can bind to all four types of FcγR types, they play a major role in antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC) [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite some differences, the most notable being the presence of N‐ glycolyl‐ instead of N‐ acetylneuraminic acid, mice share many IgG glycosylation features with humans, making them a good experimental model for examining IgG glycosylation [7–12]. When serum is used as the starting material mouse IgG glycosylation is routinely studied by ultra‐performance liquid chromatography (UPLC) [8,13,14], mass spectrometry (MS) [9,13–15], and capillary gel electrophoresis (CGE) [8].…”
Section: Figurementioning
confidence: 99%